Improving graphene gas sensors via a synergistic effect of top nanocatalysts and bottom cellulose assembled using a modified filtration technique - Duy, Le Thai; Noh, Yong Gyu; Seo, Hyungtak (Sensors and Actuators, B: Chemical, 2021)
Improving graphene properties with nanosized catalysts is of interest for numerous applications, especially chemical sensors. Thus, the aim of this study is to prepare nanocatalysts and assemble them on reduced graphene oxide (RGO) for sensing nitric oxides (NOx). The nanocatalysts used in this study include TiO2 nanoparticles (commercial) with WO3, WS2, and MoS2 nanoflakes (mechanically synthesized). Their decoration on the RGO active channel (forming nanohybrids) was obtained via a modified vacuum filtration technique, in which a small syringe and USB-powered pump were employed to surmount the limitation of the conventional filtration setup in the patternable fabrication of device arrays. Sensing measurements expose a co-effect of the nanocatalysts and the cellulose substrate on our RGO-based paper sensors. That can boost the sensitivity of RGO toward NO (1-10 ppm) and NO2 (0.7–3.5 ppm) but weaken it toward NH3 (2–20 ppm). Particularly among the nanocatalysts, MoS2 nanoflakes made our RGO nanohybrid possessing the fastest response/recovery and the highest selectivity toward NOx at room temperature (25 °C). Generally, this study reveals the synergistic effect of MoS2 and cellulose substrate on the improvement of RGO sensing ability and confirms the aptitude of our sensors for flexible and disposable NOx sensing applications.
Keywords: Cellulose substrates; Conventional filtration; Filtration techniques; Graphene properties; Nanosized catalysts; Reduced graphene oxides (RGO); Sensing applications; Synergistic effect; Graphene sensors; Nanocatalysts; Nanoflakes; Nitric oxides; Vacuum filtration